Stylistic changes in English - Uzbek translation are an example of Dale Carnegie's “How to win friends and influence people”. (Eurasian Journal of Learning and Academic Teaching, 2023)
It is during this article that stylistic change, which is one of the changes that occur during the translation process, is discussed in detail during the analysis of Dale Carnegie's “How to win friends and influence people”. Below are some examples of stylistic change to better understand this type of change.